2021
DOI: 10.1038/s41598-021-02570-y
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen deficiency results in changes to cell wall composition of sorghum seedlings

Abstract: Sorghum [Sorghum bicolor (L.) Moench] has been gaining attention as a feedstock for biomass energy production. While it is obvious that nitrogen (N) supply significantly affects sorghum growth and biomass accumulation, our knowledge is still limited regarding the effect of N on the biomass quality of sorghum, such as the contents and structures of lignin and other cell wall components. Therefore, in this study, we investigated the effects of N supply on the structure and composition of sorghum cell walls. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 89 publications
0
13
0
1
Order By: Relevance
“…Our transcriptome data shows that in LN condition, soybean roots increase expression of genes for secondary wall formation and cell wall loosening, but in LNP, no distinct behaviour can be discerned except cell wall loosening and inhibition of secondary cell wall formation. The effects of N availability on secondary cell wall formation and its components have been reported for different plants, including rice (W. , maize (Sun et al, 2018), poplar (Pitre et al, 2007), sorghum (Rivai et al, 2021), and Eucalyptus (Camargo et al, 2014), but the effects are different in different plant species. In Eucalyptus, N deprivation led to increase in lignin in secondary cell wall, but in sorghum, it caused accumulation of several hemicelluloses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our transcriptome data shows that in LN condition, soybean roots increase expression of genes for secondary wall formation and cell wall loosening, but in LNP, no distinct behaviour can be discerned except cell wall loosening and inhibition of secondary cell wall formation. The effects of N availability on secondary cell wall formation and its components have been reported for different plants, including rice (W. , maize (Sun et al, 2018), poplar (Pitre et al, 2007), sorghum (Rivai et al, 2021), and Eucalyptus (Camargo et al, 2014), but the effects are different in different plant species. In Eucalyptus, N deprivation led to increase in lignin in secondary cell wall, but in sorghum, it caused accumulation of several hemicelluloses.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of N availability on secondary cell wall formation and its components have been reported for different plants, including rice (W. Zhang et al, 2017), maize (Sun et al, 2018), poplar (Pitre et al, 2007), sorghum (Rivai et al, 2021), and Eucalyptus (Camargo et al, 2014), but the effects are different in different plant species. In Eucalyptus, N deprivation led to increase in lignin in secondary cell wall, but in sorghum, it caused accumulation of several hemicelluloses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lower nitrate concentration in the culture medium (KNO 3 0.1 mM) was also tested. Even if nitrogen has a small effect on LR number and density (Forde, 2014), it is a major element affecting CW composition and dynamics (Fernandes et al ., 2016a; Qin et al ., 2019; Rivai et al ., 2021). When grown at 0.1 mM KNO 3 , lecrk-I.9 and dominant negative mutants exhibited twice more LRs than WT, over-expressors and complemented plants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In A. thaliana , nitrate exerts its effect on LR length rather than on LR number or density (Forde, 2014). However, nitrate deficiency strongly affects both the polysaccharide composition and the enzymatic repertoire of the CW (Fernandes et al ., 2016a; Fernandes et al ., 2016b; Qin et al ., 2019; Rivai et al ., 2021). All these studies showed a decrease in cellulose content which correlated with an increase in hemicellulose and/or pectin contents.…”
Section: Discussionmentioning
confidence: 99%